TYPES OF NOUN PHRASE USED IN ARTICLE BY LISA WALLIN IN THE TRAVEL MAGAZINE - Yunus Bayan; Mu'man Mu'man (PROJECT (Professional Journal of English Education), 2022)
This article analyzed about noun phrase written by Lisa Wallin which was published in The Travel Magazine and the title is 4 Reasons for Foodies to Fall in Love with Shonai Region, Japan. The aim of this research is to find out the types of noun phrase and identify the most type which used in the Lisa Wallim’s article. Classification about types of  noun phrase by Frijuniarsi (2018) used in this article who classified noun pharse into 10 types. The researchers analyzed the data with some steps applying the descriptive qualitative and counting the each type of noun pharse to see te dominant type. The result shows that only three types of from ten type found in the Lisa Wallin’s article, they are article + noun, adjective + noun, and article + adjective + noun type. Article + noun type is dominant type which used by Lisa Wallin with 13 phrases. Keywords:  Phrase, Noun Phrase, Types of Noun Phrase